قرآن مجید کی روشنی میں سائنسی حقا‏‏ئق: تجزیاتی مطالعہ: Scientific Realities in the Light of the Quran: An analytical study - Muhammad Lateef Khan (MEI, 2023)
There has been a trend of comparison between the Quran and science. Everyone, even if he or she doesn't know any of the Quran or science, is trying unsuccessfully to find the Quran or science in the Quran. However, if the intellect is used, then there is no comparison between the Qur'an and the science, because the Qur'an is the word of Allah while science is the creature of Allah. Comparing them is nothing but foolishness. One of them is eternal and eternal, and the other is accidental. The Qur'an is not a book of science but a guide to humanity. Its subject is human and man has been sent into this world for a certain period. To explain to humans, various things in this universe have also been talked about. The knowledge of the objects of the universe is called science, so man is guided by the examples of material objects mentioned in the Quran. As time went on, man made new inventions and discoveries for his own convenience and convenience. Some of these new inventions were already mentioned in the Qur'an or they were linked to a verse in the Quran. The scientific invention was then considered as the Qur'an based on these inventions and discoveries. Here the human being stumbled and began to examine the teachings of the Quran on a scientific test. The other group of opponents of this group rejected scientific discoveries and inventions from the outset, and called for scientific knowledge. At the same time, another group that had become obsessed with the science of religion, became disillusioned with religion, and found the Quran to be inadequate and inefficient for the book of ancient people’s stories and the modern scientific era.To see if the Qur'an says something about science or scientific thinking or is it silent? Is there any connection between the Quran and science? In order to reveal the truth to all these groups, the answers to the above questions must be presented in the mirror of facts. Therefore, this article is being researched based on these points. In the thesis under consideration, science will be summarized in the context of the Quran. More details may be referred to the reference books as needed from time to time